Damage Analysis of Accommodation Space Refrigerator in Mv. Energy Pan - Bahreysy Affandi, Rifqi; Hartaya; Leonard togatorop, Agus; Baihaqi, Baihaqi (Greenation International Journal of Engineering Science, 2023)
Ships play an important role in the distribution of goods and passengers. Inside the ship there is a refrigeration machine that is used for food or other accommodation. This research examines the causes of damage to the thermal expansion valve, the emergence of frost on the evaporator pipe and reduced lubricating oil in the compressor cooling machine accommodation space. The research objective of this research is to determine the cause of damage to the thermal expansion valve, the emergence of frost on the evaporator pipe and reduced lubricating oil in the compressor. This type of research is qualitative. From the results of the study it was concluded that the cause of damage to the thermal expansion valve was the blockage of the orifice by dirt and the spring not working on the thermal expansion valve.